Thermal performance of seasonally, thermally-activated floating pile foundations in a cohesive medium. (15th September 2021) - Bodas Freitas, Teresa M.; Zito, Martina; Bourne-Webb, Peter J.; Sterpi, Donatella
Highlights: Heat exchange between piles and surrounding ground. Contextualizes reported response thermally-activated piles in cohesive media. Demonstrates influence of pile mobilisation under mechanical load on thermal response as function of: factor-of-safety on shaft resistance, pile spacing within groups. Characterises impact of heat loss from building on: Thermo-mechanical response of pile foundation, Heat exchange between piles and surrounding ground Abstract: The thermal-activation of pile foundations for use within shallow geothermal energy systems has received much attention with a number of studies having reported full- and small-scale testing and/or numerical analysis. Various conditions in terms of pile type, ground profiles and thermal loading, have been considered in these studies, leading to a broad understanding of the thermo-mechanical behaviour of thermally-activated pile foundations. One area that requires further attention is the clarification of the foundation response under seasonal cyclic thermal loading. This study systematically assesses the impact of cyclic thermal loading in relation to the initial mechanical loading, for isolated floating piles and pile groups in a cohesive soil medium. For piles where the shaft resistance dominates the pile total resistance, it was found that irrecoverable movement will be small and thermal stress and pile head movements change in a cyclic and regular manner. It is shown that the effect of the coefficient of thermal expansion of the soil, is much reduced from that suggested in studies using constant thermal loads applied over long periods. The effect of the overlying building was explored and it is shown that thermal-activation of the pile foundation mitigates the effect of the imposition of a higher average temperature at the surface.